Drugs from the Sea: A Marine Sponge-Derived Compound Prevents Type 1 Diabetes - Luc Van Kaer (The Scientific World Journal)
More than one million Americans have Type 1 diabetes. This disease — also known as autoimmune or juvenile diabetes — strikes children suddenly, makes them dependent on insulin injections for life, and carries the constant threat of devastating complications. While it can and does strike adults, nearly half of all new cases are diagnosed in children. A child is diagnosed with Type 1 diabetes every hour. Type 1 diabetes is caused by the inability of a person’s pancreas to produce sufficient amounts of insulin to control their blood sugar levels and sustain life. While insulin injections allow affected individuals to control their blood sugar and stay alive, it is not a cure nor does it prevent the devastating complications of this disease, which include kidney failure, blindness, amputations, heart attack, and stroke. In Type 1 diabetes, the body’s own immune system goes awry, attacking and destroying insulin-producing cells in the pancreas.